Brain Metabolic Dysfunction in Early Neuropsychiatric Symptoms of Dementia - Ng, Kok Pin; Chiew, Hui Jin; Rosa-Neto, Pedro; Kandiah, Nagaendran; Ismail, Zahinoor; Gauthier, Serge (Frontiers in Pharmacology, 2019)
Neuropsychiatric symptoms (NPS) including behavioral and psychiatric symptoms are common in the dementia stages of Alzheimer’s disease (AD) and are associated with poorer outcomes in cognition, functional states, quality of life, and accelerated progression to severe dementia or death. NPS are also increasingly observed in the mild cognitive impairment stage of AD and may predict incipient dementia. As such, there is an emerging conceptual framework, which support NPS as early non-cognitive symptoms of dementia. [18F]fluorodeoxyglucose positron emission tomography is a technique that is sensitive in detecting resting metabolism associated with NPS in neuropsychiatric conditions, and there is a growing body of literature evaluating the role of NPS as early indicators of brain metabolic dysfunctions in AD. In this mini-review, we examine the frequency and associations of NPS with metabolic dysfunction in the AD continuum, including preclinical, prodromal and dementia stages of AD. We will also present the validated neurobehavioral syndrome, Mild Behavioral Impairment, that describes the later life emergence of sustained NPS as an at-risk state for incident cognitive decline and dementia, and an early presentation of neurodegenerative diseases in some. Lastly, we will discuss future directions in the field so as to better understand the neurobiological basis of NPS in the early stages of the AD continuum, and their role in predicting AD pathophysiological progression and incident dementia.